2016
DOI: 10.18203/2319-2003.ijbcp20163206
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicines by patients with orthopaedic disorders in western part of India: a cross sectional study

Abstract: Medicine (NCCAM) defines CAM as a group of diverse medical and health care systems, practices and products that are not presently, considered to be a part of conventional medicine. 1 Complementary medicine is used together with conventional medicine while Alternative medicine is used in place of conventional medicine. 1Studies have documented that about half the population of many industrialized countries use traditional, complementary and alternative medicine and the proportion is as high as 80% in many devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Our findings concord with Herman et al that there is no association between using CM and income [41]. A study from India found a high proportion of CM use among those with low monthly income, which could be attributed to CM's accessibility and affordability [42], as is the case in Jordan [17,43] and other Arab countries [44] where certain plant-based preparations are deeply rooted in the tradition of disease treatment, making medicinal herbs more accessible and affordable. In contrast, more expensive supplements, such as glucosamine and chondroitin [41], are uncommon treatments in Jordan and were utilized by a negligible proportion of patients in this study.…”
Section: Plos Onesupporting
confidence: 65%
“…Our findings concord with Herman et al that there is no association between using CM and income [41]. A study from India found a high proportion of CM use among those with low monthly income, which could be attributed to CM's accessibility and affordability [42], as is the case in Jordan [17,43] and other Arab countries [44] where certain plant-based preparations are deeply rooted in the tradition of disease treatment, making medicinal herbs more accessible and affordable. In contrast, more expensive supplements, such as glucosamine and chondroitin [41], are uncommon treatments in Jordan and were utilized by a negligible proportion of patients in this study.…”
Section: Plos Onesupporting
confidence: 65%